Contribution of Pro-Inflammatory Molecules Induced by Respiratory Virus Infections to Neurological Disorders - Karen Bohmwald; Catalina A. Andrade; Alexis M. Kalergis (MDPI AG, 2021)
Neurobehavioral alterations and cognitive impairment are common phenomena that represent neuropsychiatric disorders and can be triggered by an exacerbated immune response against pathogens, brain injury, or autoimmune diseases. Pro-inflammatory molecules, such as cytokines and chemokines, are produced in the brain by resident cells, mainly by microglia and astrocytes. Brain infiltrating immune cells constitutes another source of these molecules, contributing to an impaired neurological synapse function, affecting typical neurobehavioral and cognitive performance. Currently, there is increasing evidence supporting the notion that behavioral alterations and cognitive impairment can be associated with respiratory viral infections, such as human respiratory syncytial virus, influenza, and SARS-COV-2, which are responsible for endemic, epidemic, or pandemic outbreak mainly in the winter season. This article will review the brain's pro-inflammatory response due to infection by three highly contagious respiratory viruses that are the leading cause of acute respiratory illness, morbidity, and mobility in infants, immunocompromised and elderly population. How these respiratory viral pathogens induce increased secretion of pro-inflammatory molecules and their relationship with the alterations at a behavioral and cognitive level will be discussed.